The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/jhep10(2012)026
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of two-loop master contours

Abstract: Generalized-unitarity calculations of two-loop amplitudes are performed by expanding the amplitude in a basis of master integrals and then determining the coefficients by taking a number of generalized cuts. In this paper, we present a complete classification of the solutions to the maximal cut of integrals with the double-box topology. The ideas presented here are expected to be relevant for all two-loop topologies as well. We find that these maximal-cut solutions are naturally associated with Riemann surface… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
211
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(223 citation statements)
references
References 97 publications
12
211
0
Order By: Relevance
“…For example, an elliptic integral, in which the kernel is not rational but contains a square root, enters the two-loop equal-mass sunrise graph [58,59], and it has been shown that a very similar type of integral enters a particular N 3 MHV 10-point scattering amplitude in planar N = 4 super-Yang-Mills theory [60]. However, it has been argued [61], based on a novel form of the planar loop integrand, that MHV and NMHV amplitudes can all be described in terms of multiple polylogarithms alone.…”
Section: Jhep12(2013)049mentioning
confidence: 99%
“…For example, an elliptic integral, in which the kernel is not rational but contains a square root, enters the two-loop equal-mass sunrise graph [58,59], and it has been shown that a very similar type of integral enters a particular N 3 MHV 10-point scattering amplitude in planar N = 4 super-Yang-Mills theory [60]. However, it has been argued [61], based on a novel form of the planar loop integrand, that MHV and NMHV amplitudes can all be described in terms of multiple polylogarithms alone.…”
Section: Jhep12(2013)049mentioning
confidence: 99%
“…At two or more loops many Feynman integrals can be likewise expressed in terms of GPLs [7][8][9][10][11][12][13][14][15][16][17][18][19] (for further references, see [20,21] and the references therein), but there are also integrals which are counter examples, such as notably that of the fully massive sunset graph [22][23][24][25][26]. Certain graphs without massive propagators are also believed to be counter examples [27]. In this paper we will restrict the discussion to GPLs.…”
Section: Jhep03(2016)189mentioning
confidence: 99%
“…the second option obtains an elliptic curve from the maximal cut [50][51][52][53][54][55][56] of the sunrise integral…”
Section: Beyond Multiple Polylogarithms: Single Scale Integralsmentioning
confidence: 99%